RESILIENCE OF THE EU EXPORTS TO UKRAINE UNDER THE COVID-19 PANDEMIC - Oleksandr SHNYRKOV; Oleksii CHUGAIEV (EURINT, 2020)
The paper assesses vulnerability of the EU exports to Ukraine to the current COVID-19 pandemic, which became the major challenge for societies and economies. The main current trends affecting the bilateral trade are discussed. A regression analysis is used to estimate the effects of demand and supply shocks, and changes in price competitiveness. The EU exports of fuels and road vehicles are the most sensitive to changes in the Ukraine's GDP, the exports of chemical products and telecommunication equipment - to devaluation of hryvnia. The most resilient EU exports to Ukraine included medicinal and pharmaceutical products, beverages and tobacco. The changes in consumption patterns under the quarantine measures also favoured stability of food and IT-services exports. The post-factum verification of results with the resent data confirmed most sector-specific effects. On average the EU exports to Ukraine turned out to be more resilient than to other countries.